2015
DOI: 10.3126/ajms.v6i6.12603
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid dysfunction in patients with Type 2 diabetes mellitus and its correlation with insulin resistance and serum markers for autoimmune thyroiditis

Abstract: Background:The term "THYROID DIABETES" was coined in early literature to depict the influence of thyroid hormone excess in deterioration of glucose control. Although autoimmune thyroid disease is more prevalent in Type1 Diabetes mellitus as a result of their common origin, the prevalence of hypothyroidism and hyperthyroidism is supposed to be similar to that of general population in patient with type2 DM. The purpose of the study was to evaluate the prevalence of thyroid dysfunction in patients with type2 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…While it was 1.301 ± 0.27 mIU/l and 2.596 ± 0.28 mIU/l in negative and positive groups respectively. Hormones are normally lower when serum TSH is high because of negative feedback which agrees with a previous study [7].…”
Section: Resultssupporting
confidence: 92%
“…While it was 1.301 ± 0.27 mIU/l and 2.596 ± 0.28 mIU/l in negative and positive groups respectively. Hormones are normally lower when serum TSH is high because of negative feedback which agrees with a previous study [7].…”
Section: Resultssupporting
confidence: 92%
“…The term ‘thyroid diabetes’ was initially coined in 1920 to describe the influence of thyroid hormone excess on deterioration of glucose metabolism (Rohdenburg, ; Sahu et al . ). The reason for the impaired glucose tolerance in hyperthyroidism might be because of increased hepatic glucose production, impaired insulin secretion or peripheral insulin insensitivity (Dimitriadis & Raptis, ).…”
Section: Introductionmentioning
confidence: 97%
“…12 Kahaly found that, in areas of the world where iodine intake is sufficient, autoimmune disorders represent the commonest cause of thyroid dysfunction. 13 Sahu et al (2015) found 28.33% thyroid dysfunction in type 2 diabetic patients. TPO antibody was positive in 62.07% cases of hypothyroidism and 40% cases of hyperthyroidism.…”
Section: Introductionmentioning
confidence: 98%
“…3 In addition, thyroid dysfunction is another common endocrine disorder that is also increasing day by day 4,5 and may occur in diabetic patients 6,7 especially those with autoimmune thyroid disorder. 8 Thyroid peroxidase (TPO) is an important enzyme that helps in synthesis of thyroid hormones catalyzing the oxidation of iodide on tyrosine residues in thyroglobulin. 9 TPO is a membrane-associated hemo-glycoprotein expressed only in thyrocytes and is one of the most important thyroid gland antigens.…”
Section: Introductionmentioning
confidence: 99%